Highly emissive water-soluble tetraazaperopyrenes as fluorescent markers - Hahn, Lena; Öz, Aliye Simin; Wadepohl, Hubert; Gade, Lutz H. (Chemical communications, 2014)
Water-soluble tetraazaperopyrene (TAPP) derivatives have been synthesized, which show both high photostability and high fluorescence quantum yields (>80%) in water. Furthermore delivery of the dye into cells demonstrated selective staining of the nucleus.
Gesehen am 13.10.2020